2004
DOI: 10.1128/aem.70.2.1182-1189.2004
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Survival of Campylobacter jejuni in the Phyllosphere with That in the Rhizosphere of Spinach and Radish Plants

Abstract: Campylobacter jejuni has been isolated previously from market produce and has caused gastroenteritis outbreaks linked to produce. We have tested the ability of this human pathogen to utilize organic compounds that are present in leaf and root exudates and to survive in the plant environment under various conditions. Carbon utilization profiles revealed that C. jejuni can utilize many organic acids and amino acids available on leaves and roots. Despite the presence of suitable substrates in the phyllosphere and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(47 citation statements)
references
References 42 publications
1
45
1
Order By: Relevance
“…No growth was observed in the basal defined medium (BDM) (no additional carbon source added) for any of the strains tested, allowing for the detection of carbon utilization deficiencies. High cell densities (ϳ10 8 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No growth was observed in the basal defined medium (BDM) (no additional carbon source added) for any of the strains tested, allowing for the detection of carbon utilization deficiencies. High cell densities (ϳ10 8 …”
Section: Resultsmentioning
confidence: 99%
“…In vitro binding of C. jejuni to ␣1,2-fucosylated glycans has been demonstrated previously (11,42), and free fucose reduces adherence to intestinal cells (10), suggesting recognition of this oligosaccharide by the bacterium. In addition, respiratory activity can be detected with fucose as a carbon source (8,15), although the assay identified other sugars believed to be false positives (29). In this report, we provided evidence of strain-specific utilization of fucose for Campylobacter growth.…”
mentioning
confidence: 99%
“…Survival of C. jejuni in faecal contaminated soil has also been reported by Brandl et al (2004), who demonstrated C. jejuni in soil and roots rhizosphere, long after leaves internalization had stopped. The low oxygen tension resulting from both roots and bacteria respiration at the rhizosphere supports survival of Campylobacter cells.…”
Section: Discussionmentioning
confidence: 80%
“…Brandl et al (2004) demonstrated C. jejuni in spinach roots and leaves upto 30 days post-inoculation, when temperatures were maintained at 10 to 16°C. Injured plants were shown to support survival of Campylobacter relative to healthy plants, implying post-harvest contamination of vegetables and fruits which play key role in food-safety.…”
Section: Discussionmentioning
confidence: 99%
“…Radishes (approximately 10 g) were first subjected to the removal of the soil adhering to the surface as described by Brandl et al [34] and then homogenised in Ringer's solution by a stomacher (BagMixer ® 400, Interscience, Saint Nom, France) at the maximum speed for 2 min. The decimal serial dilutions of both soil and radishes continued in Ringer's solution.…”
Section: Microbiological Analysesmentioning
confidence: 99%